Turismo gastronómico en la provincia de Tungurahua - Sáenz Segovia, Mishell Jaeline (2023)
This project responds to the need to update the typical dishes of the gastronomy of Tungurahua province before and after the pandemic and its change; with this research, it was possible to establish only those dishes that are better accepted by tourists to the study area. For this reason, it begins with the situational diagnosis through documentary research, the contribution of the provincial GAD, and the interview developed with entrepreneurs who know the gastronomic preferences of tourists; It became notorious that tourism decreased during the pandemic times and after it when the province was resuming the gastronomic tourism activity, the decrease of tourism caused gastronomy to go from 51 dishes to only 30; they disappeared for various reasons like the client’s likes and their availability. The identified post-pandemic dishes were analyzed, and, as a result they are mostly festive - every day, with low sensitivity to change and can be found more easily locally with a predominance of cooking as their principal preparation technique; within the information obtained, there is also a detail of their preparation and ingredients, with the information it developed a stocktaking according to the INPC (Instituto Nacional de Patrimony Cultural) methodology, for a better synthesis of the information obtained within the investigation. With the above mentioned, a proposal for a descriptive gastronomic guide for the province was developed, which includes: a presentation, index, tourist map with coordinates of the 30 preferential dishes, introduction, historical review, relevant information, and relevant pictures, to keep tourists informed and that they may have a mean to continue with their gastronomic journey